Screen time use patterns and health trends in children attending a children’s psychiatric outpatient department - Aldrich, Liesel (My University, 2021)
Background: Screen time use can be defined as time spent onelectronic devices; this includes computers, televisions, smartphones, gaming devices and tablets. It is hypothesised that higher amounts of screen time use could be associated with mental health conditions amongst children and adolescents. Aim: This study described screen time use patterns as well as patterns of family socialisation, sleep, eating and body mass index (BMI) and psychiatric conditions in a group of children attending the Tara Children’s Outpatient Department, Johannesburg. Methods: A convenience sample of 75 families with children and adolescents aged fiveto seventeen were recruited in the children’s clinic outpatient departmentat Tara Hospital over a nine-month period from August 2019 to May 2020. Families were invited to participate while waiting for scheduled follow up appointments. A self-report questionnaire was completed by the caregiver, and the psychiatric diagnosis was obtained from the file. Weight and height measurements were completed by the attending health care professional and attached to the questionnaire. Results: Four questionnaires were excluded from further analysis as the primary question regarding screen time use was notcompleted. All children in the sample had access to some form of device with a screen. Smartphones were the most common device the sample had access to (n=45, 69.0%). Most of the sample used more than two hours of screen time during weekdays (n=37, 52.1%) and weekends (n=62, 87.3%). The majority of the respondents reported a restriction on the amount of time the children and adolescents were allowed in front of a screen(n=52, 73.2%). The majority of children were diagnosedwith Attention Deficit Hyperactivity Disorder (ADHD) (n=52, 73.2%). Conclusion: This study is representative of a small group of families attending the Tara Children’s Outpatient Department. International and local guidelines recommend screen time use of less than two hours per day in school-goingchildren. Although parents or caregivers in this study implemented screen time use restrictions, this study noted a dissimilarity between those who implemented screen time restrictions and screen time use of less than or equal to two hours per day. Families and health care professionals should be educated about international and local recommended screen time use guidelines ,and families should be encouraged to develop their own media use plan.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine, 2021